SOFSEM 2014: Theory and Practice of Computer Science 40th International Conference on Current Trends in Theory and Practice of Computer Science,Nový Smokovec, Slovakia, January 26-29, 2014, Proceedings - Geffert, Viliam; Preneel, Bart; Rovan, Branislav; Štuller, Július; Tjoa, A Min (Theoretical Computer Science and General Issues, 2014)
This book constitutes the refereed proceedings of the 40th International Conference on Current Trends in Theory and Practice of Computer Science, SOFSEM 2014, held in Nový Smokovec, Slovakia, in January 2014. The 40 revised full papers presented in this volume were carefully reviewed and selected from 104 submissions. The book also contains 6 invited talks. The contributions covers topics as: Foundations of Computer Science, Software and Web Engineering, as well as Data, Information, and Knowledge Engineering, and Cryptography, Security, and Verification.